Family Economics Writ Large - Greenwood, Jeremy; Guner, Nezih; Vandenbroucke, Guillaume (Journal of Economic Literature, 2017)
Powerful currents have reshaped the structure of families over the last century. There has been (1) a dramatic drop in fertility and greater parental investment in children; (2) a rise in married female labor-force participation; (3) a significant decline in marriage; (4) a higher degree of positive assortative mating; (5) more children living with a single mother; and (6) shifts in social norms governing premarital sex and married women’s roles in the workplace. Macroeconomic models explaining these aggregate trends are surveyed. The relentless flow of technological progress and its role in shaping family life are stressed. (JEL D13, J12, J13, J16, J22, O33, Z13)